2016
DOI: 10.1590/abd1806-4841.20165026
|View full text |Cite
|
Sign up to set email alerts
|

Exome sequence analysis of Kaposiform hemangioendothelioma: identification of putative driver mutations

Abstract: BACKGROUNDKaposiform hemangioendothelioma is a rare, intermediate, malignant tumor. The tumor's etiology remains unknown and there are no specific treatments.OBJECTIVEIn this study, we performed exome sequencing using DNA from a Kaposiform hemangioendothelioma patient, and found putative candidates for the responsible mutations.METHODThe genomic DNA for exome sequencing was obtained from the tumor tissue and matched normal tissue from the same individual. Exome sequencing was performed on HiSeq2000 sequencer p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
3
0
1
Order By: Relevance
“…Evidence from basic research proposing that HHV8 is an integrating oncovirus that causes amplification and activation of oncogenes needs to be further investigated by the sequencing of early and advanced lesions considering the latent state in which HHV8 has been reported to exist [ 52 ] as the clonality of HHV8 integration is sometimes questioned. While many studies have been published reporting genetic alterations in KS samples, few have analysed whether these are driver mutations that might be involved in oncogenesis [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from basic research proposing that HHV8 is an integrating oncovirus that causes amplification and activation of oncogenes needs to be further investigated by the sequencing of early and advanced lesions considering the latent state in which HHV8 has been reported to exist [ 52 ] as the clonality of HHV8 integration is sometimes questioned. While many studies have been published reporting genetic alterations in KS samples, few have analysed whether these are driver mutations that might be involved in oncogenesis [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, only a few studies have focused on the initiation and progression of KHE at the genetic level. Egashira et al (42) performed exome sequencing using DNA from a patient with KHE and identified germline missense single nucleotide variants in the tumour protein p53 and adenomatous polyposis coli genes, and tumour-specific somatic mutations in the integrin subunit β2, interleukin 32 and death inducer-obliterator 1 genes. To provide effective experimental evidence for genetic diagnosis and therapy in patients with KHE/KMP, additional in vivo and in vitro studies are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…An N-terminal truncation of Dido1 (Dido1ΔNT), results in genomic instability, due to centrosome amplification and centromere localized DNA breaks (20,21), leading to myeloid malignancies (2). In the last years, several independent studies linked genetic alterations in Dido1 to different cancer types: Melanoma (22), Kaposiform hemangioendothelioma (23), Chronic Myeloid Leukemia (24), Prostate cancer (25), Head and neck cancer (26), Hepatic neuroendocrine tumours (27), Colorectal cancer (28), Bladder cancer (29), Renal cell carcinoma (30), and Esophageal cancer (31,32). Some of these studies suggested an important role of epigenetic modifications and chromatin remodelling processes in cancer development.…”
Section: Introductionmentioning
confidence: 99%